The Impact of Tidal Floods on Poor Households in the Sayung Coast, Demak Regency, Indonesia - Asrofi, Akhmad; Giyarsih, Sri Rum; Hadmoko, Danang Sri (Faculty of Geography, Universitas Gadjah Mada, 2024)
The Sayung coast is an area subject to the direct influence of coastal disasters, particularly tidal floods. Tis research aimed to investigate the impact of tidal floods on social and economic aspects in Sayung Subdistrict. In order to achieve the aim, data collection was conducted through a systematic process comprising structured interviews carried out using a questionnaire. The research also implemented a random sampling methodology, comprising a total of 23 informants and in-depth interviews were conducted with key informants to augment its comprehensiveness. Following this, the data processing and analysis followed a mixed-method approach where quantitative and qualitative data were analyzed using the Structural Equation Model (SEM) and grounded theory. The obtained results showed that tidal floods had a significant direct impact is able to influence physical health, employment, and property at 62.32%, 69.59% and and 65.43% respectively. Furthermore indirect impact property is able to influence property value by 62.78%, physical health, property damages and employment can influence mental health by 71.71% and physical health, employment can affect mobility by 66.89%. The finding accounts for a new insight that tidal floods have direct and indirect impacts on the community, as examined using the mixed-method approach. The study of tidal flood impacts on poor households in Sayung Coastal, Demak, offers different findings from previous ones. Some previous studies discuss the general effects of tidal floods while disregarding the framework of the direct and indirect impacts of the floods on poor households